Rheumatoid Lymphedema Successfully Treated with Lymphaticovenular Anastomosis: A Case Report - Ichinose, Yuko; Yasunaga, Yoshichika; Yuzuriha, Shunsuke (Journal of Reconstructive Microsurgery Open, 2019)
Background A 76-year-old woman presented with rheumatoid lymphedema (RL) distal to the left elbow after 20 years of affliction with rheumatoid arthritis (RA). Although the RA was controlled by medication, the patient could not receive full-scale compression therapy for her edema with a medium-pressure compression sleeve (pressure: 20–25 mm Hg) due to hand dysfunction caused by long-term RA.Methods Lymphaticovenular anastomosis (LVA) was performed after compression therapy with a low-pressure sleeve (14–18 mm Hg) proved ineffective for edema relief. Two anastomoses were created in a side-to-end fashion at the cubital fossa.Results The edema improved rapidly after LVA and was maintained with a low-pressure compression sleeve.Conclusion LVA represents a treatment option for remaining RL in RA treatment. As some RL patients are ineligible for full-scale compression therapy due to hand dysfunction caused by RA, LVA may help to reduce RL and enable edema management using a low-pressure compression garment without concern for hand dysfunction.
Keywords: rheumatoid arthritis; lymphedema; lymphaticovenular anastomosis